Diagnostic Role of Pediatric Appendicitis Score (PAS) in Appendicitis of Children (Journal of Paediatric Surgeons of Bangladesh, 2016)
Appendicitis is one of the most common causes of acute abdominal pain in pediatrics and is the most common indication for emergency abdominal surgery in childhood. The diagnosis of pediatric appendicitis remains challenging. To evaluate the role of pediatric appendicitis score (PAS) in the diagnosis of appendicitis of children.Methods: In this study, 200 suspected appendicitis patients attended in four private hospitals in old Dhaka city over a period of about 34 months from January 2011 to May 2014 were selected as study subjects. Patient age, sex and each of the eight PAS components were collected. Children who had PAS less than six were discharged and contacted by telephone upto 1 month to verify final outcome. Rest of the children with PAS equal or more than 6 were underwent appendectomy.Results: Two hundred patients were assessed in this study. Out of them 67 (33.5%) children had appendicitis and 76 (38.0%) children had PAS equal or more than 6. In appendicitis children, maximum (85.3%) children were in age group 10- 16 years and 10 (14.7%) patients were in age group 5-9 years.Male (73.5%) were predominant than female (26.5%) in appendicitis children. Migration of pain, nausea and anorexia were in 43 (63.2%), 45 (66.2%) and 48 (70.6%) appendicitis children respectively. Fever, cough/percussion tenderness and tenderness in RLQ were in 37 (54.4%), 52 (76.5%) and 59 (86.8%) appendicitis children respectively. Leukocytosis andneutophilia were present in 42 (61.8%) and 46 (67.6%) appendicitis children respectively. The sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV) and accuracy rate of PAS were 80.6%, 83.5%, 71.1%, 89.5% and 82.5% respectively.Conclusion: Paediatric Appendicitis Score is a good tool but not good enough for diagnosis of paediatirc appedicitis. It cannot be recommended for diagnosis of paediatric appendicitis because its negative appendicectomy rate as well as wrongly discharged rate is high.J. Paediatr. Surg. Bangladesh 6(1): 16-19, 2015 (Jan)